Novel pH-Sensitive Lipid Based Exo-Endocytosis Tracers Reveal Fast Intermixing of Synaptic Vesicle Pools - Kahms, Martin (Front Cell Neurosci, 2018)
Styryl dyes and genetically encoded pH-sensitive fluorescent proteins like pHluorin are well-established tools for the optical analysis of synaptic vesicle (SV) recycling at presynaptic boutons. Here, we describe the development of a new class of fluorescent probes based on pH-sensitive organic dyes covalently bound to lipids, providing a promising complementary assay to genetically encoded fluorescent probes. These new optical tracers allow a pure read out of membrane turnover during synaptic activity and visualization of multiple rounds of stimulation-dependent SV recycling without genetic perturbation. Measuring the incorporation efficacy of different dye-labeled lipids into budding SVs, we did not observe an enrichment of lipids with affinity for liquid ordered membrane domains. But most importantly, we found no evidence for a static segregation of SVs into recycling and resting pools. A small but significant fraction of SVs that is reluctant to release during a first round of evoked activity can be exocytosed during a second bout of stimulation, showing fast intermixing of SV pools within seconds. Furthermore, we found that SVs recycling spontaneously have a higher chance to re-occupy release sites than SVs recycling during high-frequency evoked activity. In summary, our data provide strong evidence for a highly dynamic and use-dependent control of the fractions of releasable or resting SVs.